How can NHS trusts in England optimise strategies to improve the mental health and well-being of hospital doctors? The Care Under Pressure 3 (CUP3) realist evaluation study protocol - Bramwell, C; Carrieri, D; Melvin, A; Pearson, A; Scott, J; Hancock, J; Pearson, M; Papoutsi, C; Wong, G; Mattick, K (BMJ Publishing Group, 2023)
Introduction: The growing incidence of mental ill health in doctors was a major issue in the UK and internationally, even prior to the COVID-19 pandemic. It has significant and far-reaching implications, including poor quality or inconsistent patient care, absenteeism, workforce attrition and retention issues, presenteeism, and increased risk of suicide. Existing approaches to workplace support do not take into account the individual, organisational and social factors contributing to mental ill health in doctors, nor how interventions/programmes might interact with each other within the workplace. The aim of this study is to work collaboratively with eight purposively selected National Health Service (NHS) trusts within England to develop an evidence-based implementation toolkit for all NHS trusts to reduce doctors’ mental ill health and its impacts on the workforce. Methods and analysis: The project will incorporate three phases. Phase 1 develops a typology of interventions to reduce doctors’ mental ill health. Phase 2 is a realist evaluation of the existing combinations of strategies being used by acute English healthcare trusts to reduce doctors’ mental ill health (including preventative promotion of well-being), based on 160 interviews with key stakeholders. Phase 3 synthesises the insights gained through phases 1 and 2, to create an implementation toolkit that all UK healthcare trusts can use to optimise their strategies to reduce doctors’ mental ill health and its impact on the workforce and patient care. Ethics and dissemination: Ethical approval has been granted for phase 2 of the project from the NHS Research Ethics Committee (REC reference number 22/WA/0352). As part of the conditions for our ethics approval, the sites included in our study will remain anonymous. To ensure the relevance of the study’s outputs, we have planned a wide range of dissemination strategies: an implementation toolkit for healthcare leaders, service managers and doctors; conventional academic outputs such as journal manuscripts and conference presentations; plain English summaries; cartoons and animations; and a media engagement campaign.